Curcumin: biochemistry, pharmacology, advanced drug delivery systems, and its epigenetic role in combating cancer - Smail, Shukur Wasman; Bergsten, Peter; Taha, Kalthum Othman; Yashooa, Raya Kh.; Hawezy, Dawan J.; Abbas, Muhamed Aydin; Shekha, Mudhir Sabir (Frontiers in Pharmacology, 2025)
Curcumin, the principal bioactive compound of Curcuma longa (turmeric), has received extensive scientific attention for its remarkable pharmacological and epigenetic activities, particularly in cancer prevention and therapy. This review provides a comprehensive overview of curcumin’s biochemical, pharmacological, and molecular actions. Curcumin exerts potent antioxidant, anti-inflammatory, and anticancer effects by modulating multiple signaling pathways, including NF-κB, PI3K/Akt, and Wnt/β-catenin. Despite its broad therapeutic potential, curcumin’s clinical application is limited by poor solubility, rapid metabolism, and low systemic bioavailability. To address these challenges, advanced nanotechnology-based drug delivery systems such as nanoparticles, liposomes, micelles, and polymeric carriers have been developed to enhance its solubility, stability, and targeted bioavailability. Importantly, curcumin demonstrates a multifaceted epigenetic influence that encompasses the inhibition of DNA methyltransferases leading to DNA demethylation and reactivation of silenced tumor-suppressor genes, modulation of histone acetylation and methylation balance to restore normal chromatin accessibility, regulation of non-coding RNAs such as microRNAs, lncRNAs, and circRNAs that control gene expression, and alteration of RNA methylation (m6A modification) through modulation of METTL3, FTO, and YTHDF proteins, which influence mRNA stability and translation efficiency. Collectively, these molecular and epigenetic effects reinforce curcumin’s potential as a promising multi-target agent for cancer prevention and therapy. Further pharmacogenomic and clinical studies are essential to standardize curcumin formulations and translate these preclinical findings into effective therapeutic applications.